Limited diversity of epibiont bdelloid rotifers and no pattern of codiversification with the highly diverse endemic amphipods of a coastal zone of Lake Baikal - D. Fontaneto; E. Sottoriva; A. Rodríguez-Gijón; D. Bedulina; A. Gurkov; O. A. Timoshkin; V. N. Ivanenko (The European Zoological Journal, 2023)
AbstractAn extreme radiation of hundreds of species of different groups of animals occurred in Lake Baikal, Siberia, Russia; among them, amphipods represent one of the most remarkable groups of invertebrates with about 350 endemic species. Amphipods host associated epibiont rotifers, and the aim of the study is to explore the possibility that bdelloid rotifers living as epibionts on amphipods in Lake Baikal coevolved with their hosts and diversified with species-specific host–epibiont associations. We sampled 148 individual amphipods belonging to 16 species and isolated all epibiont bdelloids from them, discovering that only one bdelloid species, Embata parasitica, lives associated with at least six amphipod species belonging to three different families. Similar to what is known in most other bdelloid species, the morphospecies Embata parasitica from Lake Baikal is likely to be a complex of cryptic species, as suggested by the high genetic diversity we found in one mitochondrial marker sequenced from several animals. Yet none of the divergent genetic lineages seemed to be associated to only one or a few amphipod species. In addition, nine bdelloid species were found living in the lake, increasing the known diversity of the area to 12 bdelloid species.